Constructing Criminological Knowledge: the Experience of the Development and Implementation of Interdisciplinary Criminology Studies at Vilnius University - Dobryninas, Aleksandras; Aleknevičienė, Jolanta; Pocienė, Aušra (Kriminologijos studijos, 2019)
Taking a social constructionists perspective, the article presents not widely known sides in the development of modern Lithuanian criminology related to the emergence, formation and development of criminological studies at Vilnius University. Since the emergence of the first criminological courses in Lithuanian academic institutions, they, as in other European continent universities, were usually taught in law faculties and schools. However, in the mid of 1990s, a unique situation occurred at Vilnius University, where sociologists and psychologists started teaching criminological courses at the Faculty of Philosophy. Later, in 1999, with the methodical help of the Faculty of Law, the teaching staff of the Faculty of Philosophy developed and implemented two-year masters programs in sociological and psychological criminology. The gained educational experience in managing and implementing interdisciplinary criminology programs at Vilnius University paved the way for introducing in 2017 new interdisciplinary bachelor study programme in criminology. On the one hand, the emergence of such studies would be impossible without long-term close and constructive collaboration between the sociologists, psychologists and lawyers of Vilnius University and, on the other, - without the active involvement of the new generation of young criminologists in the educational process. Authors emphasise, that the emergence and development of the criminology studies in Lithuania was influenced by both the developmental context of criminology at European and North American universities and the methodological and organisational support, which Lithuanian criminologists had been receiving from their colleagues from western academic institutions. Authors also present and describe the developmental process of both master and bachelor studies: they introduce the leaders, organisers and lecturers of these programs, observe their structure and inner consistency, analyse the role of interdisciplinarity in organising criminology studies. The article identifies the challenges and problems facing both the teaching and learning processes and their potential solutions, which should ensure the quality of studies, their correspondence to the state-of-art methods in criminological research and practical needs of contemporary society.